Leaf‐Inspired Patterned Organohydrogel Surface for Ultrawide Time‐Range Open Biosensing. Issue 11 (12th February 2023) - Gao, Hongxiao; Wan, Xizi; Yang, Yuemeng; Lu, Jingwei; Zhu, Qinglin; Xu, Li‐Ping; Wang, Shutao
Abstract: Droplet arrays show great significance in biosensing and biodetection because of low sample consumption and easy operation. However, inevitable water evaporation in open environment severely limits their applications in time‐consuming reactions. Herein, inspired by the unique water retention features of leaves, it is demonstrated that an open droplet array on patterned organohydrogel surface with water evaporating replenishment (POWER) for ultrawide time‐range biosensing, which integrated hydrophilic hydrogel domains and hydrophobic organogel background. The hydrogel domains on the surface can supply water to the pinned droplets through capillary channels formed in the nether organohydrogel bulk. The organogel background can inhibit water evaporation like the wax coating of leaves. Such a unique bioinspired design enables ultrawide time‐range biosensing in open environment from a few minutes to more than five hours involving a variety of analytes such as ions, small molecules, and macromolecules. The POWER provides a feasible and open biosensing platform for ultrawide time‐range reactions. Abstract : The authors prepare a novel droplet array on patterned organohydrogel surface with water evaporating replenishment (POWER), enabling ultrawide biosensing time from minutes to hours with negligible sample diffusion. The POWER platform can be applied to almost all biosensing with different time ranges in an open environment, shedding new light on the design of next‐generation water retention platforms without additional equipment appendix.